2005
DOI: 10.1002/path.1775
|View full text |Cite
|
Sign up to set email alerts
|

Roles for USF‐2 in lung cancer proliferation and bronchial carcinogenesis

Abstract: The upstream stimulatory factors USF-1 and USF-2 dimerize to regulate transcription through E-box motifs in target genes. Although widely expressed, they can mediate tissue-specific transcription and we previously reported that USF-2 can enhance transcription of arginine vasopressin, a neuropeptide growth factor in small cell lung cancer. Here we determine the expression and role of USF-2 in lung cancer subtypes and examine USF-2 distribution in the bronchial epithelium. For a panel of 12 cell lines and 10 fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
0
26
0
Order By: Relevance
“…USF2 not only contains a functional cleavage site but also the full-length protein is cleaved in trans by Taspase1. As USF2 dimerizes with USF1 to regulate transcription through E-box motifs in target genes (44), cleavage of USF2 might be sufficient to attenuate the activity of this transcriptional regulator complex, as no cleavage site could be detected in USF1 (supplemental Fig. S5).…”
Section: Discussionmentioning
confidence: 99%
“…USF2 not only contains a functional cleavage site but also the full-length protein is cleaved in trans by Taspase1. As USF2 dimerizes with USF1 to regulate transcription through E-box motifs in target genes (44), cleavage of USF2 might be sufficient to attenuate the activity of this transcriptional regulator complex, as no cleavage site could be detected in USF1 (supplemental Fig. S5).…”
Section: Discussionmentioning
confidence: 99%
“…While a number of studies support the idea of GSK3β being tumor suppressive, others studies showed that GSK3β may promote cancer development [72]. Similar findings were obtained with respect to USF2; being tumor suppressive with respect to prostate cancer [8], [73] but being rather promoting in the development of lung cancer [74] and thyroid cancer [75]. Although no study has yet correlated the activity of GSK3β with the activity of USF2 in a certain tumor setting, the findings of the present study would favor the tumor promoting aspects of GSK3β and USF2 since GSK3β activated USF2 enhanced cell migration which may be important in terms of tumor cell metastasis.…”
Section: Discussionmentioning
confidence: 60%
“…A reintroduction of an intact human chromosome 19 into a tumorigenic prostate cell line reduced tumorigenicity in athymic nude mice [59]. In addition, USF2 was found to be affected in breast [9], lung [11], oral [10] and colorectal [60] cancer suggesting a more general role of USF2 in tumorigenesis. This suggestion is supported by reports showing that USF2 also regulates the expression of the APC, BRCA2 and p53 tumor suppressor genes [61][63] and our previous studies showing that USF2 plays an important role in regulating the expression of the cancer marker PAI-1 [21], [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…uSF1 mRNA expression is downregulated in LACs compared with that in normal tissues (44). In lung cancer, uSF1 and uSF2 dimerize to mediate the transcription via E-box motifs in target genes (45). Moreover, with the E-box motif, uSF1 activates GATA5 gene expression (46), which is pivotal in cell differentiation and tissue development in lung cancer (47,48).…”
Section: Discussionmentioning
confidence: 99%